2009
DOI: 10.1007/s00018-009-8765-7
|View full text |Cite
|
Sign up to set email alerts
|

Chitotriosidase and gene therapy for fungal infections

Abstract: Chitotriosidase secreted by activated human macrophages has been implicated in the defence against chitin-bearing pathogens. The antifungal properties of human chitotriosidase were investigated here following retroviral vector-mediated gene transfer of the open reading frame of the chitotriosidase gene into Chinese hamster ovary cells. A chitinase assay confirmed that the engineered cells secreted recombinant chitotriosidase constitutively. Two dimensional gel electrophoresis and western blotting indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 31 publications
(29 reference statements)
0
42
1
Order By: Relevance
“…Increased ChT activity was also recorded in several other diseases, such as Niemann-Pick (Brinkman et al 2005), GM1 gangliosidosis , b-thalassemia (Barone et al 1999), sarcoidosis (Boot et al 2010), malaria (Barone et al 2003), atherosclerosis (Artieda et al 2003;Boot et al 1999), and fungal and bacterial infections (Iyer et al 2009;Labadaridis et al 1998). The role of ChT enzyme is unclear, but a possible role in defense against chitin-containing pathogens and host immune response has been suggested (Choi et al 2001;Di Luca et al 2007;Di Rosa et al 2005;Gordon-Thomson et al 2009;Malaguarnera et al 2005;van Eijk et al 2005).…”
Section: Discussionmentioning
confidence: 98%
“…Increased ChT activity was also recorded in several other diseases, such as Niemann-Pick (Brinkman et al 2005), GM1 gangliosidosis , b-thalassemia (Barone et al 1999), sarcoidosis (Boot et al 2010), malaria (Barone et al 2003), atherosclerosis (Artieda et al 2003;Boot et al 1999), and fungal and bacterial infections (Iyer et al 2009;Labadaridis et al 1998). The role of ChT enzyme is unclear, but a possible role in defense against chitin-containing pathogens and host immune response has been suggested (Choi et al 2001;Di Luca et al 2007;Di Rosa et al 2005;Gordon-Thomson et al 2009;Malaguarnera et al 2005;van Eijk et al 2005).…”
Section: Discussionmentioning
confidence: 98%
“…It has been suggested that CHIT1 has a role in the defense towards chitin containing pathogens [19] however elevated expression of CHIT1 has also been associated with a range of human diseases that have no obvious connection to chitin containing pathogens. These include Gaucher type I disease [20], Alzheimer's disease [21][22][23], type B Niemann-Pick disease [24], sarcoidosis [25,26], atherosclerosis [27], multiple sclerosis [28,29] and scleroderma-associated lung disease where CHIT1 has even been proposed as a potential therapeutic target [30].…”
mentioning
confidence: 99%
“…Recent in-vivo and in-vitro studies suggest that ChT is involved at multiple points in different inflammatory and infectious diseases [10,[17][18][19][20][21] although the molecular mechanism of the ChT is far from being completely resolved in these conditions [10,22]. It was reported increased plasma ChT activity in neonates with fungal infection [10].…”
Section: Discussionmentioning
confidence: 99%